Antioxidant and Physicochemical Properties of Chokeberry Pomace as Valuable Food Industry By-Product - Amela Kusur; Amel Selimović; Sedina Hodžić (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Chokeberry (Aronia melanocarpa) pomace is by-product generated after juice extraction from aronia berries. It represents a solid residue that contains significant amounts of antioxidants, dietary fiber, and other nutritionally valuable ingredients. The transformation of by-products into valuable products and food ingredients should be carried out promptly to ensure a safe and stable product, with drying of the pomace being the first step of the valorization process. In this study, chokeberry pomace was dried at 50°C to a final moisture content of approximately 8%. After drying and cooling, the pomace was ground and subjected to analysis. The greatest value of pomace lies primarily in its high content of bioactive compounds. The results showed that the pomace contained high levels of polyphenols (5923.37±249.31 mg GAE/100 g DM), flavonoids (598.47±30.07 mg CtE/100 g DM), as well as high antioxidant capacity determined by the FRAP assay (88.51±4.40 mmol Fe2+/100 g DM), and DPPH assay (31.93±0.09 mmol TE/100 g DM). The IC50 value was 10.66±3.30 µg/mL, indicating strong radical scavenging ability. In addition to the antioxidant capacity, physicochemical properties (moisture content, water activity, pH value, titratable acidity, ash content, sugar content and color) were also determined. Based on these findings, chokeberry pomace has the potential to be used as a functional ingredient in food products to enhance their nutritional value, antioxidant potential, and sensory properties.